Key issues in using information systems for strategic marketing decisions. (1st January 2001) - Li, Shuliang; Davies, Barry J.
This paper deals with some key issues in using and developing information systems for strategic marketing decisions. Firstly, managerial requirements for information systems support are examined. Secondly, the current status of information systems usage for strategic marketing decision-making is explored. Finally, the problems of existing support systems and the potential of hybrid intelligent support systems are discussed. It is concluded that hybrid intelligent support systems, coupled with such techniques as group decision support and knowledge management, will have a part to play in support of strategic marketing decisions, with the decision makers as a core and in control.